2020
DOI: 10.1007/s00431-020-03834-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and risk factors of lactic acidosis in children with acute moderate and severe asthma, a prospective observational study

Abstract: Lactic acidosis is a common complication of status asthmaticus in adults. However, data is sparse in children. The aim of this study was to describe the prevalence and risk factors for lactic acidosis in children hospitalised for acute moderate or severe asthma. A total of 154 children 2–17 years of age were enrolled in a prospective observational study conducted in a tertiary hospital. All had capillary blood gas assessment 4 h after the first dose of salbutamol in hospital. The primary endpoint was the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In a recent prospective study by Ruman-Colombier et al on children admitted with acute, moderate, and severe asthma, 26% presented with lactic acidosis (lactate > 5 mmol/l and AG ≥ 16 mmol/l), and nebulized salbutamol was a risk factor [12]. Furthermore, Rodrigo et al showed that high lactate concentrations can develop during the first hours of inhaled β2-agonist treatment in adult patients with severe acute asthma treated with high doses of albuterol [7].…”
Section: Discussionmentioning
confidence: 97%
“…In a recent prospective study by Ruman-Colombier et al on children admitted with acute, moderate, and severe asthma, 26% presented with lactic acidosis (lactate > 5 mmol/l and AG ≥ 16 mmol/l), and nebulized salbutamol was a risk factor [12]. Furthermore, Rodrigo et al showed that high lactate concentrations can develop during the first hours of inhaled β2-agonist treatment in adult patients with severe acute asthma treated with high doses of albuterol [7].…”
Section: Discussionmentioning
confidence: 97%
“…The proposed mechanism of SILA lies in the hyperadrenergic state it induces [ 5 ]. Salbutamol-induced hyperadrenergic drive promotes glycolysis, glycogenolysis and gluconeogenesis, which leads to overproduction of pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…This hyperadrenergic state also enhances lipolysis, resulting in free fatty acids that inhibit the entrance of pyruvate into the Krebs cycle via inhibition of pyruvate dehydrogenase, thus shunting pyruvate into the anaerobic pathway [ 6 , 7 ]. Moreover, systemic corticosteroid use frequently induces a state of hyperglycaemia, which potentially provides more substrate for lactic acid production [ 5 ]. Corticosteroids also enhance β 2 -receptor sensitivity, perpetuating the vicious cycle of a hyperadrenergic state and increased lactate production [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above diseases, AG is closely related to asthma. Asthma can affect the normal gas exchange of the human body, cause hypoxemia, respiratory muscle fatigue, anaerobic metabolism occurs, cause metabolic acidosis, and AG in patients is often increased 8 . High AG levels, which represent hypoxia and tissue hypoperfusion, are more common in patients with worsening asthma, suggesting a poor prognosis 9 .…”
Section: Introductionmentioning
confidence: 99%